Voice and pronunciation of cochlear implant speakers - Horga, Damir (Array, 2006)
Patients with cochlear implants have the ability to exercise auditory control over their own speech production and over the speech of others, which is important for the development of speech control. In the present investigation three groups of 10 subjects were compared. The groups comprised: 1. cochlear implant users, 2. profoundly deaf using traditional hearing aids and 3. hearing controls. The subjects in three groups were matched in age. While repeating after a model the subjects were recorded and the following linguistic voice variables were analysed: 1. vowel formant space, 2. voice vs. voiceless difference, 3. closure duration and VOT, 4. word accent production, 5. sentence stress production, 6. voice quality, 7. pronunciation quality. Acoustic analysis and perceptual assessment by phoneticians showed that in great majority of variables, subjects with cochlear implants performed better than the profoundly deaf subjects with traditional hearing-aids.